Higher order regularized trace formula for the regular Sturm-Liouville equation contained spectral parameter in the boundary condition - Bayramoglu, Mehmet; Sahinturk, Hulya (ELSEVIER SCIENCE INC, 2007)
In this paper we have obtained a formula for order >= 2 regularized trace for a regular Sturm-Liouville equation with operator coefficient and contains spectral parameter in the boundary condition. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: eigenvalue problem; spectral parameter in boundary conditions; nuclear operator; EIGENVALUE; Mathematics